Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
2x-9=-x+6
+x +x
3x-9=6
+9 +9
3x=15
x=5
therefore the equations have one solution (x=5)
+x +x
3x-9=6
+9 +9
3x=15
x=5
therefore the equations have one solution (x=5)
since we want to find solutions that will work for both of the equations, we must first assume that x and y are both the same in both so
y=2x-9
y=-x+6
we make the second equation negative by multiplying the whole thing by -1 and get
-y=x-6
add this to the first equation
y-y=x+2x-9-6
0=3x-15
add 15 to both sides
15=3x
divide both sides by 3
5=x
subsitute 5=x for x in the second equation
y=-x+6
y=-5+6
y=1
y=2x-9
y=-x+6
we make the second equation negative by multiplying the whole thing by -1 and get
-y=x-6
add this to the first equation
y-y=x+2x-9-6
0=3x-15
add 15 to both sides
15=3x
divide both sides by 3
5=x
subsitute 5=x for x in the second equation
y=-x+6
y=-5+6
y=1
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.